1988
DOI: 10.1080/03079458808436506
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of laying turkeys with Rhinotracheitis virus: Distribution of virus in the tissues and serological response

Abstract: SUMMARYTwenty-four laying turkey hens shown to be free of antibodies to turkey.rhinotracheitis virus were inoculated intranasally with an isolate of the virus. A mild respiratory disease developed between 5 and 9 days post infection (pi). Two birds were selected at random at intervals between days 1 and 20 pi, killed and tissues examined for the presence of virus. At autopsy between days 2 and 12 abnormalities were found in the oviducts including the deposition of inspissated albumen. Yolk material was occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 7 publications
4
48
0
3
Order By: Relevance
“…Cilia may allow the virus to attach and therefore it may be suggested that polarized epithelial cells are the main target cells of aMPV (Jones et al, 1986;O'Loan & Allan, 1990;Majó et al, 1995;Jirjis et al, 2001;Zhang et al, 2002). In the present state of knowledge, the oviduct epithelium is the only other surface susceptible to aMPV, apart from respiratory epithelia (Jones et al, 1988). In addition, it has been suggested that macrophages may carry the virus and act as vectors within the host (Sharma et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cilia may allow the virus to attach and therefore it may be suggested that polarized epithelial cells are the main target cells of aMPV (Jones et al, 1986;O'Loan & Allan, 1990;Majó et al, 1995;Jirjis et al, 2001;Zhang et al, 2002). In the present state of knowledge, the oviduct epithelium is the only other surface susceptible to aMPV, apart from respiratory epithelia (Jones et al, 1988). In addition, it has been suggested that macrophages may carry the virus and act as vectors within the host (Sharma et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate the need for a larger sampling size when attempting to isolate APV. Jones et al (1988) found IF to be more sensitive than virus isolation in the case of turkeys and also to give results more quickly (Jones, 1996). Catelli et al (1998) compared virus isolation with an IP assay for the detection of APV in young, experimentally inoculated SPF chickens and found that each method detected the virus in nasal turbinate tissue for a similar period of time.…”
Section: Sampling Sizementioning
confidence: 99%
“…Techniques involving the use of IP Majó et al, 1995), IF Jones et al, 1986Jones et al, , 1988 and immunogold staining (O'Loan et al, 1992) have all been reported for the detection of APV in turkeys. In addition, IF and IP (Majó et al, 1995;Catelli et al, 1998) techniques have been used successfully to detect APV in chickens.…”
Section: Immunochemical Assaysmentioning
confidence: 99%
See 2 more Smart Citations